1999
DOI: 10.1007/s002590050405
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced stunning continues for at least one hour: evaluation with quantitative gated single-photon emission tomography

Abstract: To elucidate the after-effect of exercise on left ventricular (LV) function, end-diastolic volume (EDV), end-systolic volume (ESV) and ejection fraction (LVEF) were evaluated at 1 h after exercise and at rest by technetium-99m tetrofosmin gated myocardial single-photon emission tomography (SPET) using an automated program in 53 subjects. The subjects were grouped as follows: normal scan (n = 16), ischaemia (n = 19) and infarction (n = 18), based on the interpretation of perfusion images. Postexercise LVEF did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
4

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 12 publications
2
20
0
4
Order By: Relevance
“…Numerous recent reports using 99m Tc-based radiopharmaceuticals and various methods of inducing stress have shown that poststress LVEF is significantly lower than resting LVEF in patients with myocardial ischemia [11,12,13]. The current study showed similar findings, with the mean LVEF being significantly lower on early poststress images than on delayed images among patients with myocardial ischemia but not those with only fixed defects.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Numerous recent reports using 99m Tc-based radiopharmaceuticals and various methods of inducing stress have shown that poststress LVEF is significantly lower than resting LVEF in patients with myocardial ischemia [11,12,13]. The current study showed similar findings, with the mean LVEF being significantly lower on early poststress images than on delayed images among patients with myocardial ischemia but not those with only fixed defects.…”
Section: Discussionsupporting
confidence: 92%
“…This phenomenon has also been observed in humans, and is referred to as postischemic myocardial stunning [10]. Such a finding was recently reported during myocardial perfusion imaging that was started 30 min to 1 h post stress using various 99m Tc tracers and different stress agents [11,12,13,14].…”
Section: Introductionmentioning
confidence: 91%
“…[1][2][3] In the studies about poststress gated SPECT functional changes, the time interval between tracer injection and poststress imaging ranged from 15 minutes to more than 60 minutes, and there was no direct comparison between different delays. 1,2,[19][20][21][22][23][24][25][26][27][28] Recently, Toba et al 3 reported that in patients with single-vessel CAD, a very early (10 minutes) poststress gated SPECT study was superior to the usual 30-and 50-minute intervals to identify transient decreases in EF in the subjects with stress-induced ischemia, and they confirmed the relationship between severity of ischemia and degree of functional impairment. To our knowledge, their study is the only one addressing the issue of ischemiarelated functional changes by comparing different acquisition delays.…”
Section: Acquisition Delay and Ischemia-related Functional Changesmentioning
confidence: 79%
“…25 Paul et al reported similar results and showed that the extent of stress-induced LVEF depression was determined by the severity of ischemia, not by the fi xed defect. 27 For patients in the fi xed defect group, poststress stunning was seen in 42 of 90 patients (46.7%). This was consistent with the results reported previously by Bavelaar-Croon et al who found, using Tc-99m tetrofosmin, that 33 of 58 patients (57%) with sustained myocardial infarction showed statistically signifi cant deterioration of LV function (>2% decrease) that persisted as long as 30 min after stress.…”
Section: Discussionmentioning
confidence: 97%